DETERMINAN KEJADIAN STUNTING PADA BALITA - Afriza, Renita; Sulistyowati, Endang; Apidianti, Sari Pratiwi; Simamora, Janner Pelanjani (Ensiklopedia of Journal, 2024)
Abstract: Stunting is a chronic nutritional problem that occurs due to a lack of nutritional intake over a long period of time, caused by feeding that is not in accordance with the body's nutritional needs. In North Bengkulu, the number of stunted toddlers was recorded at 1,899 children, with details of 1,640 toddlers classified as short and 259 toddlers who were very short. This figure shows a significant increase in stunting cases in North Bengkulu. The purpose of the study was to determine the determinants of the incidence of stunting in toddlers. The research design used in this study was cross sectional. The research was conducted in the working area of the Kerkap Health Center. The research was conducted in May 2023. The study population was toddlers aged 24-59 months in the Kerkap Health Center working area, totaling 593 children. The sample amounted to 90 respondents selected using stratified random sampling. The research instrument used a research questionnaire. Data analysis was done univariate and bivariate. The results showed there was a relationship between LBW (p value: 0.035) and exclusive breastfeeding history (p value: 0.007) to the incidence of stunting. It is recommended to pregnant women and mothers who have toddlers to provide exclusive breastfeeding and to the Puskesmas to further optimize the socialization program for pregnant women to prevent LBW and stunting so that every family member has a good nutritional status including children, so that the stuting nutritional status that occurs in children aged 24-60 months can change and get better at a later age.Keywords: Exclusive breastfeeding, LBW, stunting.